Economics of Eucalyptus Plantation-with Special Reference to Uttar Pradesh - Mathur, R. S.; Sagar, S. R.; Ansari, M. Y. (Indian Forester, 1984)
Large scale plantation of Eucalyptus were started in 1962 in the tarai region of U.P. in mixed poor stocked forests or grassy blanks within or c1osor to the forests. The total area upto 1978-79 under Eucalyptus plantations in different forest circle of U.P. was 82,132 hectare while the total area under all other broad leaved species was 5,39,180 ha. At present Eucalyptus is raised in large scale plantation programme by the Forest Department as well as by the individuals all over the country. The present study is concerned with 116 hectare Eucalyptus plantations which were established in 13 different plots during 1971 and 1973, in the Bijnor Plantation Division. Main crop of these plantation was exloited during 1981-82, and produced 4895 & 951S m3 (Q G) logs and firewood for which royalty received this study reveals that Eucalyptus plantations are economically feasible.